Exploring Gender Differences in Coding at the Beginning of Primary School - Montuori, Chiara; Ronconi, Lucia; Vardanega, Tullio; Arfé, Barbara (Frontiers in Psychology, 2022)
The gender gap in Computer Science (CS) is widely documented worldwide. Only a few studies, however, have investigated whether and how gender differences manifest early in the learning of computing, at the beginning of primary school. Coding, seen as an element of Computational Thinking, has entered the curriculum of primary school education in several countries. As the early years of primary education happen before gender stereotypes in CS are expected to be fully endorsed, the opportunity to learn coding for boys and girls at that age might in principle help reduce the gender gap later observed in CS education. Prior research findings however suggest that an advantage for boys in coding tasks may begin to emerge already since preschool or the early grades of primary education. In the present study we explored whether the coding abilities of 1st graders, at their first experience with coding, are affected by gender differences, and whether their presence associates with gender differences in executive functions (EF), i.e., response inhibition and planning skills. Earlier research has shown strong association between children's coding abilities and their EF, as well as the existence of gender differences in the maturation of response inhibition and planning skills, but with an advantage for girls. In this work we assessed the coding skills and response inhibition and planning skills of 109 Italian first graders, 45 girls and 64 boys, before an introductory coding course (pretest), when the children had no prior experience of coding. We then repeated the assessment after the introductory coding course (posttest). No statistically significant difference between girls and boys emerged at the pretest, whereas an advantage in coding appeared for boys at the posttest. Mediation analyses carried out to test the hypothesis of a mediation role of EF on gender differences in coding show that the gender differences in coding were not mediated by the children's EF (response inhibition or planning). These results suggest that other factors must be accounted for to explain this phenomenon. The different engagement of boys and girls in the coding activities, and/or other motivational and sociocognitive variables, should be explored in future studies.